INOVASI PEMBELAJARAN SENI TARI BERBASIS ANDROID DI MASA COVID 19 - Reni Veliyanti; Dani Sasmoko; Indra Irawan Wahyudi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
During Covid 19 the learning process experienced very severe obstacles, one of the 03semarang Elementary School and Elementary School 01 Semarang. In this study the Android application was used to support the dance learning system where students had to learn their own dance arts at home using the Android application. From the interviews conducted as many as 66.3 % like learning with mobile phones and 72.1 % understand the theory in the Android application so that when learning with mobile phones can easily understand. But for learning the practice of dance 54.7 % does not understand it. This may be the video displayed is not suitable for elementary students so you need a suitable learning video for learning that requires movement.